2001
DOI: 10.1063/1.1428412
|View full text |Cite
|
Sign up to set email alerts
|

Traps at the bonded interface in silicon-on-insulator structures

Abstract: In this study, we compared the trap density distributions, D it , in the band gap of silicon at the Si/thermal SiO 2 interface and at the bonded interface of the silicon-on-insulator structure, deduced from deep level transient spectroscopy measurements. The trap energies for the bonded Si/SiO 2 interface are localized in the range from E c -0.17 to E c -0.37 eV. The lack of the transient SiO x layer at the bonded interface is suggested to lead to a relatively narrow interval of trap energies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…7,8 In this method, the energy levels contributing predominantly to the Q-DLTS signal at a current temperature and chosen time window were calculated from the equation…”
Section: Experimental and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 In this method, the energy levels contributing predominantly to the Q-DLTS signal at a current temperature and chosen time window were calculated from the equation…”
Section: Experimental and Resultsmentioning
confidence: 99%
“…Recently, we showed that the spectrum of traps at a bonded Si/SiO 2 interface substantially differs from that at an Si/SiO 2 interface prepared by thermal oxidation. 7,8 This difference was attributed to the absence of the transition SiO x layer at the bonded interface or/and intense neutralization of traps by hydrogen due to utilization of hydrogen slicing technology ͑hydrogen implantation in one of the bonded wafers͒. The concentration of hydrogen present in SOI during fabrication can be lowered if one uses BESOI technology.…”
mentioning
confidence: 96%
“…It should be mentioned that in simulations, the traps energy level, density, and distribution in the interface (D it ) are defined according to [22][23][24][25].…”
Section: Pixel Descriptionmentioning
confidence: 99%
“…When the annealing temperature increases from 900 to 1100°C, the trap density decreases from 2 · 10 12 cm À2 to 2.5 · 10 11 cm À2 . An information about the activation energy of the traps located at the Si/SiO 2 interface for bulk materials was obtained by deep level transient spectroscopy [9]. The values are located in the 0.17-0.37 eV interval.…”
Section: Introductionmentioning
confidence: 99%